(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Freshly harvested fruits of the tall and dwarf cultivar of the variety Sharbati were evaluated at three different storage temperatures (-5 to -6 0 C, 4 to 6 0 C and 40 to 45 0 C) with subsequent peel and seed drying or freeze drying to determine the appropriate cultivar, its storage life and optimum falconoid retention in dried pulp. FTIR studies and optimization of process conditions involving extraction techniques (SAE, MAE and UAE), extraction solvents (ethanol, methanol, petroleum ether and water), extraction time and temperature were carried out on the selected cultivar using RSM. In the case of SAE, the time ranged from 1 to 4 h, 15 to 60 min (UAE) and 3 to 12 min for MAE, while the temperature varied from 500C to 1100C for MAE and from 350C to 80C for SAE and UAE. For ethanol, methanol and petroleum ether, the concentration of S olvent ranged from 55 to 100 percent when water was used in its pure state. The finding shows that for better preservation of flavonoids and other biochemical constituents for a longer period of time, the dwarf cultivar, deep freeze storage and freeze drying condition were considered optimal. Constituents for longer periods of time. In the case of SAE, optimized conditions for optimized temperature, time and temperature conditions, time and solvent concentration were 64.090C, 2.72 h, 77.72 percent (methanol), for maximum total flavovoid content (TFC) and 65.45 0C, 2.57 h, 77.27 percent (ethanol), for ex-traction yield, respectively. For the UAE, we obtained maximum TFC quantity and extraction yield at 64.54 0C, 37.72 min, 70.00 percent (methanol) while for MAE, at 76.060C, 9.81 min. 75.00 percent (ethanol). In the case of SAE and UAE, the highest concentrations of TFC were obtained using methanol, while ethanol was found to be the strongest MAE extraction solvent.